EVALUATION OF RISK MANAGEMENT POLICIES OF THE FEDERAL UNIVERSITIES CONCERNING COMPLIANCE WITH NORMATIVE INSTRUCTION 01/2016: EVALUATION OF RISK MANAGEMENT POLICIES OF THE FEDERAL UNIVERSITIES CONCERNING COMPLIANCE WITH NORMATIVE INSTRUCTION 01/2016 - Pinto, Joseane Batalha; Nogueira, Ricardo Jorge da Cunha Costa; Cerquinho, Kleomara Gomes (Brazilian Journal of Production Engineering, 2020)
In the corporate world, companies are exposed to a significant amount of uncertainty. For this reason, it is essential to manage risks within organizations. The first rule dealing with the subject in the public sector - IN No. 01/2016 MP/CGU - is just over 4 years old and was issued jointly by the Ministry of Planning, Budget and Management and the Comptroller General of the Union. This study aims to evaluate the degree of compliance of Federal Universities with the directives contained in the IN regarding the elaboration of the Risk Management Policy, RMP, as well as to understand Risk Management in the public sector and to analyze the content of the documents produced by the institutions. For the purposes outlined, a documental research of an applied nature and a quantitative approach was chosen. The degree of compliance with the IN proved to be quite balanced, as 51.11% of the policies complied with more than half of what the regulations established, which shows that there was dedication for the RMP to be prepared with a view to the effective implementation of Risk Management. The methodologies, tools, forms and periodicity of risk assessment and monitoring had low occurrence in policies, as it involves the operationalization of the Risk Management process, still little known by Universities, which need a greater degree of maturity in the subject.
Keywords: Risk Management; Federal Universities; Risk Management Policies